“Merasa malu” dan “kurang kesadaran berpartisipasi”: tantangan wanita usia subur dalam screening kanker serviks melalui tes inspeksi visual dengan asam asetat - Sarah Asifa; Endang Sutisna Sulaeman; Heni Hastuti; Ari Natalia Probandari (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
“Embarrassment” and “lack of awareness”: challenges for reproductive women in cervical cancer screening through visual inspection with acetic acid testPurpose: This study aims to explore the challenges for reproductive women in cervical cancer screening through visual inspection with acetic test in Surakarta.Method: A survey was conducted involving distribution of questionnaires to 382 women aged 16-49 years from 5 public health centers.Results: Most respondents were 21-30 years old (40,1%), married (97,1%), as a housewife (59,2%), and had higher school education (60,5%). Had no sex education (OR: 2,00; 95%CI: 1,04-3,86) and low awareness (OR: 3,07; 95%CI: 1,25-7,49) were significantly associated with the low coverage of VIA Test. On the other hand, had no embarrassment (OR: 0,63; 95%CI: 0,41-0,99) was negatively associated with the low coverage of VIA Test.Conclusion: Awareness, sex education, and embarrassment were associated with the VIA Test Coverage at community health center in Surakarta. Specific strategies and programs that addresses these factors are needed to increase the coverage of VIA Test.